Data on the geology and mineralogy of the oil shale occurrence at Pula, Hungary - Mezősi József; Mucsi Mihály (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1976)
The gravelly sand of basaltic and basalt tuff substance forming the basement of the oil shale and the overlying alginite was taken stratigraphically one rhythm. So the sequence overlies directly the erosion surface of the Upper Triassic dolomite. In its roof carbonate mud, humic clay and aleurite are found. The oil shale is of rhythmic structure locally with thick (several metres) "massive" oil shale intercalations. The lower ten metres of the bore Put—7 is alginitic carbonate mud of massive type with a few coalified plant remnants. The ostracod half-shells and Diatomaskelets are frequent. This is overlain in about 10 m thickness by carbonate-muddy alginite of inhomogeneous structure with the remnants of Botryococcus colonies and diatoma-skelets. Above it thin aleurite intercalation is found which is followed by alginite of massive type down to 15 m and this is replaced by clay marl and sandy aleurite of 1 to 1.5 m thickness. Between 8 and 13 metres alginitic aleurite, aleuritic alginite and carbonate mud alternate, then carbonate mud and clay marl, finally clayey aleurite follow. The formations are for the most part built up by minerals of predominantly micron size, thus these were determined by means of X-ray diffractometer. The percentual determination of the individual phases was impossible just because of the locally widespread amorphous material. The frequent minerals of the bore's formation are as follows: aragonite, calcite, dolomite, quartz and locally feldspar, and clay mineral also frequently occurs. In the lower section of 20 metres aragonite plays a predominant role. Small quantities of calcite, dolomite are characteristic, the quartz is sometimes absent, the feldspar is subordinated. Between 20 and 5 m three smaller sections can be separated where aragonite is absent and is replaced by calcite and dolomite. It has been determined that in spite of its instable structure aragonite may remain when the enclosing rock is clayey, less permeable, or oil shale. In our case both criteria exist. The possibility of formation of aragonite is explained by the fact that the lagoon enclosed by the ring-shaped tuff barriers of the volcanic crater had been heated by ' the subsequent hot springs so there was a possibility to CaC03 to precipitate in form of aragonite. In the bore the periodical occurrence of aragonite and the change in the mineral composition are explained by the fact that this lake of warmer water was periodically inundated by colder water of higher salt concentration from outside. During these phases the precipitation of aragonite ceased, the grain size of the sediment changed and quartz becomes predominant, in general.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok